UPAYA HICOLLEAGUES DALAM MEMPERTAHANKAN BRAND ENGAGEMENT MELALUI MEDIA SOSIAL TIKTOK - Azizy, Azizy; Gifa, Alkausara Putri; Larasati, Mayra Azzahra; Kurniasari, Ni Gusti Ayu Ketut (IAHN Gde Pudja Mataram, 2024)
The purpose of this research is to analyze the marketing communication approach strategy via social media TikTok Hicolleagues, which aims to increase Brand Engagement. The method used is descriptif qualitatif with model The Circular Model of Some, a method that integrates user interaction, content analysis, and the influence of communication strategies on Brand Engagement. Data was collected through observation and FGD with five participants.The research results show that interactive and creative content strategies, such as challenges, collaborative videos, use of the latest trends, and quick responses to comments and active participation in interactions are successful in attracting audience attention and increasing Brand Engagement. Implementation of The Circular Model of Some' enables in-depth and comprehensive analysis of the effectiveness of HiColleagues' digital marketing communications strategy.